MERANCANG LEMBAGA KEUANGAN MIKRO SYARIAH YANG TEPAT PADA DESA PABANGBON, KECAMATAN LEUWILIANG, KABUPATEN BOGOR - Thantawi, Tubagus Rifqy; Rizal, Muhammad; Aprilia, Annisa (Jurnal Pengabdian Kepada Masyarakat Perbankan Syariah: Program Studi Perbankan Syariah., 2025)
This community service aims to design a Sharia Microfinance Institution (LKMS) model that is in accordance with the economic characteristics of Pabangbon Village. The subject of this community service is the people of Pabangbon Village, Leuwiliang District, Bogor Regency, West Java Province. In this community service, activities are carried out based on methods with a Participatory Action Research (PAR) approach which is oriented towards community empowerment. The result of this community service is to produce a design of the right type of sharia microfinance institution for Pabangbon Village, namely in the form of a Sharia Financing Savings and Loan Cooperative (KSPPS) in Pabangbon Village, Leuwiliang District, Bogor Regency. With this community service, it is hoped that it can provide solutions to improve the economic level of the community, especially inclusive financing, empowering local business actors, and improving the welfare of the Pabangbon Village Community through the implementation of sustainable sharia economy-based financial services.